Biochar and biostimulant in forming Schinus terebinthifolius seedlings1 - Santos, Felipe P. dos; Lima, Ana P. L. de; Lima, Sebastião F.; Silva, Arlindo A. P. da [UNESP]; Contardi, Lucymara M. [UNESP]; Vendruscolo, Eduardo P. (FapUNIFESP (SciELO), 2022)
The use of new products, such as biochar and biostimulants, has the potential to accelerate growth and improve the quality of seedlings that will be taken to the field. Therefore, this study aimed to evaluate the influence of biochar and plant biostimulant on the formation of Schinus terebinthifolius seedlings. The experiment was installed in randomized blocks arranged in a 5 × 2 factorial scheme with four replications. Biochar proportions in the substrate composition (0, 7.5, 15, 22.5 and 30%) in the presence (15 mL L-1) or absence of biostimulant in the seed treatment were evaluated. Stem diameter, height, leaf area, root length and volume, and shoot and root dry mass were measured at 100 days after sowing. Relationships were calculated from these parameters, which determine the quality of seedlings. The combined use of biochar and biostimulant influences the formation and quality of Schinus terebinthifolius seedlings, with this association being beneficial for the root development of seedlings. Biochar is viable and may be added to the substrate mixture for producing S. terebinthifolius seedlings. The proportions containing around 15% of biochar presented seedlings with the highest quality. The use of biostimulant allows for adding higher quantities of biochar to be mixed in the substrate. Taller plants have larger stem diameters and root lengths. Plants with larger root volumes provide better seedling quality, evidenced by the higher Dickson quality index.
Biocarvão e bioestimulante na formação de mudas de Schinus terebinthifolius
Keywords: fine coal; substrate; vegetable regulators